2021
DOI: 10.1186/s43045-021-00145-1
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and depression in the elderly due to COVID-19 pandemic: a pilot study

Abstract: Background The elderly are a vulnerable section of the population who are prone to physical, mental, social, and economic deprivation. The effect of COVID-19 had a worldwide impact on all age groups, with a particularly higher mortality and morbidity rate among the elderly population. The present study was undertaken to know about the psychological morbidity in the geriatric population during the period of the COVID-19 pandemic. The study was cross-sectional and was done through a telephonic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
1
22
1
1
Order By: Relevance
“…We did not find any study that reports the COVID-19-related anxiety level among the older population during the COVID-19 pandemic in Bangladesh using the CAS. However, a recent study among older people in India using the Geriatric Anxiety Scale [ 37 38 ] reported an anxiety prevalence of 8.7%, which is lower to what we have found in our study. Existing Bangladeshi studies on University students [ 23 , 24 ], young people [ 39 ], health workers [ 40 ] and the general population [ 41 , 42 ] reported anxiety prevalence during the COIVD-19 pandemic, ranging from 40 to 70%.…”
Section: Discussioncontrasting
confidence: 99%
“…We did not find any study that reports the COVID-19-related anxiety level among the older population during the COVID-19 pandemic in Bangladesh using the CAS. However, a recent study among older people in India using the Geriatric Anxiety Scale [ 37 38 ] reported an anxiety prevalence of 8.7%, which is lower to what we have found in our study. Existing Bangladeshi studies on University students [ 23 , 24 ], young people [ 39 ], health workers [ 40 ] and the general population [ 41 , 42 ] reported anxiety prevalence during the COIVD-19 pandemic, ranging from 40 to 70%.…”
Section: Discussioncontrasting
confidence: 99%
“…At the follow-up examination of this cohort, inflammatory markers were also the predictors of depression and anxiety in addition to a prior psychiatric history, although gender was not. However, Das et al (2021) [ 27 ] found that among the older population (>60 years), anxiety and depression were present at the rates of 8.7% and 15.2%, respectively.…”
Section: Reviewmentioning
confidence: 99%
“…In some studies, anxiety and depression increased particularly due to reasons such as physical problems, movement limitations, and dependency on others [ 21 , 22 , 23 ]. Some studies, on the contrary, showed lower levels of anxiety and depression, and they motivated this result with a possible higher resilience and coping mechanisms in older people in comparison to the younger population or with a greater acceptance of death with maturity developed by age [ 24 , 25 ]. Moreover, when one considers resilience in the context of the COVID-19 pandemic, a few studies have shown that older people seem to better manage their emotional and psychological consequences [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%